ANALISIS SISTEM DAN PROSEDUR PEMBERIAN KREDIT DENGAN JAMINAN BPKB MOTOR PADA PT. NUSANTARA SURYA SAKTI CABANG ENDE - Haba, Cindy S D; Marselina, Apriana; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2021)
PT. The Nusantara Surya Sakti branch, Ende, is engaged in two business fields, namely trading, and services. which includes Nusa Surya Cipta (NSC) which is engaged in financing and cash guaranteed by BPKB Motor and Nusantara Surya Sakti (NSS) which serves the purchase of motorbikes and motorbikes. In the field of cash financing with BPKB Motor (Honda, Yamaha, or Kawazaki) guarantees. The purpose of this study was to analyze the system and procedures for granting credit with a motorcycle BPKB guarantee at PT Nusantara Sakti Branch Ende in accordance with the Standard Operating Procedure (SOP). The method used by the author in this research is descriptive qualitative, which is an article that describes the actual situation regarding the System and Procedure of Credit Provision with the BPKB Guarantee Agency. Nusantara Surya Sakti Ende Branch. The results of this study are systems and procedures for granting credit with a motorcycle BPKB guarantee at PT. Nusantara Surya Sakti Branch Ende which researchers found is part of the procedure for granting credit with collateral. BPKB has complied with Standard Operating Procedures (SOP), but credit is still lacking, even though there is still a shortage of credit. The system used often experiences network errors/interferences, human errors are caused by employees who experience fatigue and lack of concentration. The analysis has applied 5C (Character, Capacity, Capital, Collateral, Condition) especially Capacity (ability) and Condition (economic condition)